Narrativas transmedia de jóvenes y adultos mayores: una propuesta de alfabetización multimodal, crítica y emancipadora (2023)
The purpose of this research is to guide pedagogical practices that, from the multimodal and narrative perspective configure other ways of literacy in young people and older adults. In order to achieve this purpose, it is necessary to investigate the concepts of adult education, transmedia storytelling in education and reading and writing processes in the classroom.